A peony-leaves-derived liquid corrosion inhibitor: protecting carbon steel from NaCl. Issue 4 (2nd October 2017) - Honarvar Nazari, Mehdi; Shihab, Mehdi Salih; Cao, Ling; Havens, Eden Adele; Shi, Xianming
ABSTRACT: A liquid mixture was developed from waste peony leaves through a zero-waste chemical/biological process. The inhibition effect of different concentrations of peony leaves derived solution (0–3 vol.%, PLS0-3) on C1010 carbon steel in 3.5 wt.% NaCl was investigated over time using electrochemical measurements. Chemical analyses were performed to reveal the main compounds of this inhibitor. Surface analyses together with water contact angle measurements were employed to study the characteristics of the steel surface affected. Semi-empirical calculations with PM3 method were used to find the relationship between molecular structure and inhibiting effect of PLS. The inhibitor was stable over time and its main active ingredients were C19 H27 N4 O10 P and C17 H16 N3 O9 P that adsorb onto the steel surface, block cathodic active sites, make the surface hydrophobic, decrease the surface free energy, and facilitate the formation of a passive layer. A good correlation was found between experimentally determined inhibition efficiency and theoretically calculated properties of PLS. GRAPHICAL ABSTRACT: